Phytochemical-rich Eucommia ulmoides leaf extract extends healthspan in Caenorhabditis elegans via the pmk-1/p38 MAPK pathway and mitochondrial homeostasis - Zhang, Jiaxu; Ma, Quhuan; Li, Jiaojiao; Xie, Xingwen; Shi, Xiaofeng (Frontiers in Nutrition, 2025)
ObjectivesAs a medicinal and edible resource, Eucommia ulmoides leaf (EUL) shows considerable promise in facilitating healthy aging. However, its precise biological mechanisms remain unclear. This study aimed to investigate the anti-aging efficacy and underlying pathways of Eucommia ulmoides leaf extract (EULE) using the Caenorhabditis elegans (C. elegans) model.MethodsPhytochemical profiling of the extract was performed. C. elegans were supplemented with the extract, and the effects on lifespan, healthspan indicators (muscle deterioration, intestinal barrier function, mitochondrial homeostasis), and gene expression were evaluated via transcriptomic analysis.ResultsPhytochemical analysis revealed that the extract is abundant in bioactive compounds such as flavonoids, iridoids, and lignans. Supplementation with the extract significantly prolonged the lifespan of C. elegans by up to 14.69% and improved healthspan by alleviating age-related muscle deterioration, preserving intestinal barrier function, and regulating mitochondrial homeostasis. Transcriptomic analysis identified the mitogen activated protein kinase (MAPK) signaling pathway as the primary mediator of these anti-aging benefits.ConclusionsThese results provide robust evidence supporting the use of EUL as a natural dietary supplement to prolong healthspan, establishing a scientific rationale for its application in promoting healthy aging.